2009
DOI: 10.1080/08934210903061587
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the Relationship between Self-Esteem, Commitment, and Verbal Aggressiveness in Romantic Dating Relationships

Abstract: Using sociometer theory (Leary, 1999), this study investigated the relationships between argumentativeness and verbal aggressiveness, self and partner's perceived commitment levels, and self-esteem within romantic dating relationships. Survey results (n ¼ 152) indicated that 1) a moderate relationship between one's self-esteem and one's perceived partner's commitment level existed, 2) a positive correlation between one's self-esteem and level of self-commitment existed, 3) self-esteem was negatively correlated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 30 publications
1
14
1
1
Order By: Relevance
“…We hypothesized that commitment would be in some way related, as Rill et al (2009) showed that low commitment may induce a sense of rejection in women and, thus, may lead to body image dissatisfaction (Duemm et al, 2003). However, our results did not find this to be the case.…”
Section: Relations Of Commitment To Body Image Dissatisfactioncontrasting
confidence: 57%
See 1 more Smart Citation
“…We hypothesized that commitment would be in some way related, as Rill et al (2009) showed that low commitment may induce a sense of rejection in women and, thus, may lead to body image dissatisfaction (Duemm et al, 2003). However, our results did not find this to be the case.…”
Section: Relations Of Commitment To Body Image Dissatisfactioncontrasting
confidence: 57%
“…Thus, it is perhaps not surprising that relationship commitment is related to body satisfaction, especially in females as women worry more than men that their partners' attraction to them will wane if they gain weight (Campbell, 2001). Thus, the relationship between commitment and body satisfaction may exist because romantic partners may interpret or perceive low commitment as a form of rejection (Rill, Baiocchi, Hopper, Denker, & Olson, 2009). If they believe this rejection is based on their body size and shape, it could lead to even lower body satisfaction and disordered eating behaviors to compensate for the rejection (Duemm, Adams, & Keating, 2003).…”
Section: Relationship Commitmentmentioning
confidence: 99%
“…One consistent finding in research demonstrating effects of dating abuse on adjustment is the negative impact of abuse upon an individual's self-esteem (Göncü & Sümer, 2011;Katz et al, 2000;Rill et al, 2009;Robinson & Cameron, 2012). Using traditional definitions of physical, emotional, and sexual dating abuse, studies have found lowered self-esteem, increased feelings of inferiority, and self-defeating beliefs among victims (Göncü & Sümer, 2011;Longmore & Demaris, 1997;Sawangchareon et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The goal of the present study was to investigate the relationship between cyber dating abuse and self-esteem in a sample of emerging adults (i.e., those within the period from the late teens through the twenties; Arnett, 2000). More specifically, our goal was to examine how reactions of emotional distress could mediate or explain the expected relationship between the experience of cyber dating abuse and decreased self-esteem (Katz, Arias, & Beach, 2000;Rill et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation